An observational study of extending FOLFOX chemotherapy, lengthening the interval between radiotherapy and surgery, and enhancing pathological complete response rates in rectal cancer patients following preoperative chemoradiotherapy. (September 2016) - Huang, Chun-Ming; Huang, Ming-Yii; Tsai, Hsiang-Lin; Huang, Ching-Wen; Ma, Cheng-Jen; Yeh, Yung-Sung; Juo, Suh-Hang; Huang, Chih-Jen; Wang, Jaw-Yuan
Introduction: Patients with rectal cancer who exhibit a pathologic complete response to preoperative concurrent chemoradiotherapy have excellent oncologic outcomes. In this study, we evaluated the potential advantages of adding oxaliplatin to preoperative fluoropyrimidine-based chemoradiotherapy administered in rectal cancer patients. Methods: A total of 78 patients with rectal cancer were enrolled. Patients were administered chemoradiotherapy, which comprised radiotherapy and chemotherapy involving a 5-fluorouracil, leucovorin, and oxaliplatin regimen every 2 weeks. Surgery was performed 10–12 weeks after radiotherapy completion. Tumor regression, adverse events, surgical complications, and short-term clinical outcomes were recorded. Results: Two patients were excluded because of incomplete radiotherapy treatment or refusal of surgery. Eventually, 76 patients underwent total mesorectal excision and no perioperative mortality was observed. Of these, 20 patients (25.6%) developed grade 3 or 4 toxicity during concurrent chemoradiotherapy. Among the 76 patients who underwent surgery, 24 (31.6%) patients achieved a pathologic complete response. The sphincter preservation rate was 96.1% (73/76) in all patients and 92.2% (39/42) in patients with tumors located less than 5 cm from the anal verge. The 2-year overall and disease-free survivals were 94% and 87.4%, respectively. Conclusion: The intensified multimodality therapy was well tolerated in our cohort and resulted in a considerably high pathologic complete response rate. Regardless of favorable short-term clinical outcomes, long-term oncologic outcomes will be closely monitored among the patients with a pathologic complete response.